Two endoplasmic reticulum proteins (calnexin and calreticulin) are involved in innate immunity in Chinese mitten crab (Eriocheir sinensis) - Huang, Ying (Sci Rep, 2016)
Calnexin (Cnx) and calreticulin (Crt), which are important chaperones in the endoplasmic reticulum (ER), participate in the folding and quality control of client proteins. Cnx and Crt identified from Chinese mitten crab (Eriocheir sinensis) are designated as EsCnx and EsCrt, respectively. EsCnx and EsCrt are expressed in the hemocyte, hepatopancrea, gill, and intestine at the mRNA and protein level. Immunofluorescence analysis indicated that EsCnx and EsCRT are located in the ER. Moreover, the mRNA and protein expression levels of EsCnx and EsCrt were altered by challenge with lipopolysaccharides (LPS), peptidoglycans (PGN), Staphyloccocus aureus, and Vibrio parahaemolyticus. Recombinant EsCnx and EsCrt (rEsCnx and rEsCrt, respectively) proteins can bind to various Gram-positive and Gram-negative bacteria, as well as to different polysaccharides (LPS and PGN). rEsCnx and rEsCrt assisted in the clearance of V. parahaemolyticus in vivo, and the clearance efficiency was impaired after silencing of EsCnx and EsCrt. Our results suggest that the two ER proteins are involved in anti-bacterial immunity in E. sinensis.